2005
DOI: 10.1007/s11920-005-0024-5
|View full text |Cite
|
Sign up to set email alerts
|

How does studying schizotypal personality disorder inform us about the prodrome of schizophrenia?

Abstract: An increasing emphasis in the schizophrenia literature has been on the prodromal phase of the illness. The study of schizophrenia spectrum illness, including schizotypal personality disorder, has added important insight into the etiology, neuropathology, and treatment of schizophrenia, which can facilitate early identification, intervention, and perhaps prevention of the illness. The heterogeneity of the schizophrenia spectrum makes its definition elusive at best. The primary aim of the Cognitive Assessment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 61 publications
(101 reference statements)
4
45
0
Order By: Relevance
“…Participants included 48 (26M/22F) individuals between the ages of 12 and 30 (Mean Age=18.6 years, S.D.=4.2) who met CARE criteria (Seeber and Cadenhead, 2005) for being at risk for schizophrenia and had participated in the study a minimum of one year. All subjects were administered the Structured Interview for Prodromal Syndromes (SIPS) (Miller et al, 2003) and met at least one of 4 at risk states, as described in Table 1.…”
Section: Participantsmentioning
confidence: 99%
“…Participants included 48 (26M/22F) individuals between the ages of 12 and 30 (Mean Age=18.6 years, S.D.=4.2) who met CARE criteria (Seeber and Cadenhead, 2005) for being at risk for schizophrenia and had participated in the study a minimum of one year. All subjects were administered the Structured Interview for Prodromal Syndromes (SIPS) (Miller et al, 2003) and met at least one of 4 at risk states, as described in Table 1.…”
Section: Participantsmentioning
confidence: 99%
“…The Cognitive Assessment and Risk Evaluation (CARE) Program (Seeber and Cadenhead 2005) is a referral clinic that provides longitudinal assessment and treatment of individuals aged 12 to 30 who are considered at risk for schizophrenia or are experiencing their first episode of the illness. Study participants included subjects that are considered to be "at risk" for developing schizophrenia, "first episode" patients who first met diagnostic criteria for schizophrenia within the last year, and "normal comparison" subjects from the community.…”
Section: Methodsmentioning
confidence: 99%
“…All participants also received a comprehensive clinical, neurocognitive, and psychophysiologic battery that includes an Axis I diagnostic interview (Structured Clinical Interview for DSM-IV Axis I Disorders [SCID] (First et al 1995) or Kiddie Schedule for Affective Disorders and Schizophrenia [KSADS] (Kaufman et al 1996)), Structured Interview for Prodromal Syndromes (SIPS) (Miller et al 1999), assessment of family history information using Family History -Research Diagnostic Criteria (FHRDC) (Andreasen et al 1977), and Structured Interview for DSM-IV Personality (SIDP) (Pfohl et al 1995). First episode patients were not administered a SIPS or SIDP (Seeber and Cadenhead 2005). During the clinical interview, subjects were also queried about their developmental history.…”
Section: Methodsmentioning
confidence: 99%
“…Schizophrenia and SPD share phenomenologic and genetic similarities that have been vital in the development of prospective criteria for identifying the "prodrome" of schizophrenia, a period of warning signs and symptoms (including deterioration in functioning) which eventually converts to a clear presentation of a psychotic illness such as schizophrenia [6]. By definition, the prodrome is a retrospective diagnosis but great effort has been made to identify demographic and clinical criteria which can then be used to identify "putatively prodromal," "high-risk," "ultra-high risk," or "at-risk" individuals who may progress to a psychotic illness.…”
Section: Schizophrenia Prodromementioning
confidence: 99%
“…In a preliminary report [6], we have assessed a subgroup of at-risk subjects in the P50 paradigm and prepulse inhibition (PPI) paradigm, another measure of central inhibition that has been found to be reduced in patients with schizophrenia, their first-degree relatives, and in individuals with SPD. In this report, we found that there was a divergence of performance in the P50 and PPI paradigms in at-risk subjects, similar to a previous report on SPD [30].…”
Section: P50 Event-related Potential Sensory Gatingmentioning
confidence: 99%